Manuscripts in Sumenep Madura; the Legacy of Pesantren and its Ulama - Zakiyah Zakiyah (Center for Research and Development of Religious Literature and Heritage, 2017)
There are more than a hundred manuscripts that were found in Sumenep Madura and were digitized by a research team from the Office of Religious Research and Development Ministry of Religious Affairs, Semarang Indonesia. That research focused on the identification and digitalization on those manuscripts; however, that research has not made further analysis on the content. Therefore, this paper examines the content of those manuscripts and classifies them into category based on the discipline. In addition, this essay looks at how these manuscripts related to pesantren and its ulama (kyai/Muslim scholars) in Sumenep Madura. This study uses a library research and content analysis method. The result shows that from the 107 digitized manuscripts, there are more than 107 texts embedded in those manuscripts, since some of the manuscripts are a compilation book. The majority of those manuscripts consist of fiqh texts (64 texts), followed by tauhid/theology (46 texts), tasawuf/mysticism (8 texts), Qur’an (3 manuscripts), Arabic grammar and linguistic (6 texts), and the rests are texts about do’a, Javanese horoscope and history. All of those texts are written in an Arabic letter and used various languages such as Arabic, Javanese and Madurese. Some of those manuscripts are collection of ulama and pesantren in that area. These ulama and pesantren received their manuscripts from their parents and preserved it until now. Indeed, those manuscripts can be recognized as the legacy of pesantren and its ulama in Sumenep Madura. In the context of Sumenep Madura, ulama/kyai and pesantren play significant roles in the development of Islam since they are the center of the society.